Difference between revisions of "1983 AHSME Problems/Problem 18"
Sevenoptimus (talk | contribs) m (Added box at the bottom) |
|||
(4 intermediate revisions by 2 users not shown) | |||
Line 1: | Line 1: | ||
− | Problem | + | ==Problem== |
+ | |||
Let <math>f</math> be a polynomial function such that, for all real <math>x</math>, | Let <math>f</math> be a polynomial function such that, for all real <math>x</math>, | ||
− | < | + | <math>f(x^2 + 1) = x^4 + 5x^2 + 3</math>. |
− | For all real <math>x | + | For all real <math>x, f(x^2-1)</math> is |
− | (A) | + | <math>\textbf{(A)}\ x^4+5x^2+1\qquad |
+ | \textbf{(B)}\ x^4+x^2-3\qquad | ||
+ | \textbf{(C)}\ x^4-5x^2+1\qquad | ||
+ | \textbf{(D)}\ x^4+x^2+3\qquad | ||
+ | \textbf{(E)}\ \text{none of these} </math> | ||
− | Solution | + | ==Solution== |
− | Let <math>y = x^2 + 1</math>. Then <math>x^2 = y - 1</math>, so we can write the given equation as | + | Let <math>y = x^2 + 1</math>. Then <math>x^2 = y - 1</math>, so we can write the given equation as |
− | \begin{align*} | + | <cmath>\begin{align*}f(y) &= x^4 + 5x^2 + 3 \\ |
− | f(y) &= x^4 + 5x^2 + 3 \\ | ||
&= (x^2)^2 + 5x^2 + 3 \\ | &= (x^2)^2 + 5x^2 + 3 \\ | ||
&= (y - 1)^2 + 5(y - 1) + 3 \\ | &= (y - 1)^2 + 5(y - 1) + 3 \\ | ||
&= y^2 - 2y + 1 + 5y - 5 + 3 \\ | &= y^2 - 2y + 1 + 5y - 5 + 3 \\ | ||
− | &= y^2 + 3y - 1. | + | &= y^2 + 3y - 1.\end{align*}</cmath> |
− | \end{align*} | + | Then substituting <math>x^2 - 1</math> for <math>y</math>, we get |
− | Then substituting <math>x^2 - 1</math>, we get | + | <cmath>\begin{align*}f(x^2 - 1) &= (x^2 - 1)^2 + 3(x^2 - 1) - 1 \\ |
− | \begin{align*} | ||
− | f(x^2 - 1) &= (x^2 - 1)^2 + 3(x^2 - 1) - 1 \\ | ||
&= x^4 - 2x^2 + 1 + 3x^2 - 3 - 1 \\ | &= x^4 - 2x^2 + 1 + 3x^2 - 3 - 1 \\ | ||
− | &= | + | &= x^4 + x^2 - 3.\end{align*}</cmath> |
− | \end{align*} | + | The answer is therefore <math>\boxed{\textbf{(B)}}</math>. |
− | The answer is (B). | + | |
+ | ==See Also== | ||
+ | {{AHSME box|year=1983|num-b=17|num-a=19}} | ||
+ | |||
+ | {{MAA Notice}} |
Latest revision as of 00:55, 20 February 2019
Problem
Let be a polynomial function such that, for all real , . For all real is
Solution
Let . Then , so we can write the given equation as Then substituting for , we get The answer is therefore .
See Also
1983 AHSME (Problems • Answer Key • Resources) | ||
Preceded by Problem 17 |
Followed by Problem 19 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 • 26 • 27 • 28 • 29 • 30 | ||
All AHSME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.